IMPLEMENTASI PENDEKATAN PEMBELAJARAN MENDALAM (DEEP LEARNING) DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA DI SEKOLAH DASAR - Wibowo, Gandi Wibowo; Deni Gunawan; Dinny Mardiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Elementary education faces transformative challenges in the 21st century, where learning practices are not merely about knowledge transfer but require the development of deep conceptual understanding in students. This research aims to obtain information/overview, identify, and analyze the impact of implementing a deep learning approach in enhancing students' conceptual understanding in elementary schools. The research subjects consisted of fifth-grade teachers and students in elementary schools. This study used a qualitative case study approach with data collection techniques conducted through participant observation, in-depth interviews, and documentation studies. The implementation stages were based on the deep learning process: understanding, applying, and reflecting. The results show that the implementation of a deep learning approach, which includes indicators of mindful learning, meaningful learning, and joyful learning, has a positive impact on improving students' conceptual understanding in IPAS (Science, Social Studies, and Arts) learning. Due to limitations in the research subjects, future researchers are advised to expand the scope of subjects and subjects, and to conduct further quantitative research to statistically test the effectiveness of deep learning on improving student learning outcomes.